The Functions of Code Switching on Teaching Speaking for EFL Students - Sushy Teko Patanduk; Normalia Sirande; Aris Kaban Sendana; Matius Tandikombong (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Language will be acquired and mastered due to habitual factors. In the case of second language learning in higher education, it is expected that the use of English as language instruction is needed to improve students ability in Speaking. In fact, in the learning process, code-switching is still carried out by lecturers, and result of some studies shows that students respond positively to the it. The purpose of this study is to find out the function of code-switching carried out by lecturers in Speaking classes at UKI Toraja. Researchers used quantitative descriptive methods. This research population are lecturers who perform code-switching in Speaking courses in the classroom at UKI Toraja. Total sampling is used in sample selection with interviews as a tool for collecting data. The results of the study processed using quantitative descriptive methods. The result shows that lectures switch code in teaching Speaking for several functions. They are: a. to introduce new topic b. to create good learning atmosphere. c to build effective, flexible and non-rigid communication d. as a strategy to facilitate and check student understanding e. to minimize the students’ levels of anxiety in conveying their ideas.